Preparation of operating room for COVID-19 suspects at a tertiary care teaching hospital in New Delhi, India - Sodhi, Jitender; Gupta, Anant; Singh, Gurpreet; Singh, Gagandeep; Kumar, Rajeev; Kapil, Arti; Sahni, Peush (International Journal of Infection Control, 2022)
The continuous rise in the number of cases of COVID-19, caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), generated an urgent need to transform the facilities of our existing operating rooms (OR) to cater for emergency surgeries for patients with suspected COVID-19. The aim was to minimise the spread of infection and to achieve the lowest risk for patients and staff while caring for COVID-19 suspects undergoing surgery. We devised a protocol in our hospital to prepare OR for patients suspected to be suffering from COVID-19 but in whom the surgical intervention could not be deferred until the result of the COVID-19 test was obtained. The key consideration was that we cater to suspected and confirmed COVID-19 patients who required emergency surgery while adhering to strict infection control measures. The study was undertaken as a pilot exercise in consultation with treating surgeons, hospital infection control committee members, hospital administrators, and engineers, along with a literature review, to transform the design and functioning of existing facilities to prepare for emergency surgeries of COVID-19 suspects at the beginning of the pandemic. While this required significant planning on paper and onsite by members of the OR staff, hospital infection control committee, administration, and engineers, the creation of a safe operating environment was possible within a 48-h period with minimal structural alterations.